Bridging disciplines through Alzheimer care: A faculty-guided summer interprofessional education experience for prelicensure nursing students. - Cox, Catherine Wilson; Farina, Crystel L.; Reisenberg, Catherine E.; Charles, Rashida (Nursing, 2026)
Interprofessional education (IPE) is essential for preparing nursing students to engage in collaborative, team-based care. However, coordinating IPE experiences is challenging for several reasons, including the limited number of health profession programs with summer enrollment. The Accelerated Bachelor of Science in Nursing (ABSN) program at the authors' university operates year-round on a four-semester schedule, making it difficult to ensure consistent IPE opportunities for every cohort, particularly those beginning in summer. To address this gap and advance best practices, the authors present a redesigned virtual simulation structured as an IPE experience that offers meaningful interdisciplinary engagement for summer-entry ABSN students.